Lightning Air Terminal Collection Volume Assessment: A New Technique and Device - Zainuddin Nawawi; Hussein Ahmad; Muhammad Abu Bakar Sidik; Lim Pai Hung; Aulia Aulia; Hamizah Shahroom; Muhammad Irfan Jambak (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2015)
For buildings, structures and facilities a Lightning Protection System (LPS) is very important. There are some components that affect the effectiveness of LPS. One of the components is the lightning air terminal. With reference to the facilities requiring lightning protection the position, the apparent height, and the angle of protection of lightning air terminals determines the collection volume (CV) of the protected area. The CV of direct strike lightning air terminals can change because of the facility is affected by natural disasters such as seismic tremor and flood. If such natural disasters do happen, there are possibilities that the facilities will not be fully protected from direct lightning strikes. The building and structure could be misalignment after the seismic tremor and flood related to earth movement. So for the safety of equipment and personnel, lightning protection system efficacy assurance is necessary. Therefore, there should be a technique and device to monitor the variation of collection volume afforded by every lightning air terminal on buildings and structures after the occurrence of a natural disaster. This paper presents a new technique as well as a new device to monitor the collection volume variation. A part of the device was obtained from a recycled moveable television antenna. This approach is not only practical, portable and cost effective but also incorporating the idea of environmental protection and recycling of used plastic materials.